Evaluation of stress-strain for characterization of the rheological behavior of alginate and carrageenan gels - Mammarella,E.J. (2002)
The stress-strain of samples deformed until failure and the relaxation response after 50% deformation of the initial height under constant stress were obtained. Uniaxial compression and stress-relaxation tests enabled satisfactory differentiation of the mechanical resistance of gels with different alginate and carrageenan concentrations. Higher values for initial force at the beginning of the relaxation test were associated with higher calcium uptake by the gels. An increment of failure stress during the uniaxial compression tests for higher concentration of calcium in the gel structure was also observed. The maximum amount of cation uptake was higher than the theoretical value for saturation of all the carboxylic groups available in alginate molecules due to structural rearrangements. Stress-relaxation tests indicated that the residual stress of the gel increased with kappa-carrageenan concentration.